AICCRA-Mali inception and stakeholder’s engagement workshop - Arinloye, Djalal A.; Sanogo, Kapoury; Bayala, Jules; Dossou-Yovo, Elliott Ronald (Accelerating Impacts of CGIAR Climate Research for Africa, 2021)
The report presents the key outcomes from the inception workshop held in Bamako, Mali from on 26 and 27 Oct. 2021. It presents stakeholder's reflections on integrated rice–tree systems with most suitable and adapted tree species, the benefits of integrating tree species into the rice landscape, the most practical CSA technologies to deal with climate change, and major constraints for gender-inclusive adoption and scaling of the technologies.